Chemical composition and biological activity of the essential oil from Thymus lanceolatus - Khadir, Abdelmounaim; Sobeh, Mansour; Peixoto, Herbenya; Sporer, Frank; Ashour, Mohamed L.; Wink, Michael (Zeitschrift für Naturforschung. C, a journal of biosciences, 2016)
Thymus lanceolatus is a rare species, which grows wild in Algeria and Tunis. It is used traditionally as a drink and to flavor and preserve meat and poultry. The composition of the essential oil was determined by GLC/FID and GLC/MS. Forty-nine components were identified and quantified, accounting for 96.75% of the total detected components in the oil. The oxygenated monoterpenes (74.85%) constitute the major class of volatile secondary metabolites in the oil. Thymol was the most abundant constituent (69.61%) followed by γ-terpinene (8.38%). The antioxidant activity was evaluated using both diphenylpicrylhydrazyl (DPPH˙) reduction and 2-deoxyribose (2-DR) degradation prevention methods. The oil showed a very potent antioxidant activity with IC50 values of 0.20 ± 0.07 and 4.96 ± 0.39 μg/mL for the DPPH˙ and 2-DR methods, respectively. The antimicrobial activity of the oil was assessed using the agar diffusion method, and the in vitro cytotoxicity on five different cancer cells was examined using the MTT assay. The oil revealed promising inhibitory activity against Gram positive bacteria, especially Bacillus subtilis and Streptococcus pyogenes with an MIC value of 62.5 μg/mL. Additionally, the highest cytotoxic activity was observed against the HL-60 cells with an IC50 of 113.5 μg/mL. These results validate some of their traditional uses in food preservation.
Gesehen am 01.02.2017